Two hundred years of the Brazilian economy (according to Liberals, Nationalists, and Marxists): dependency as a project? - Zahluth Bastos, Pedro Paulo (Araucaria, 2022)
The paper presents stylized facts about the two hundred years of Brazilian economic history according to classical liberals, nationalists, and Marxists. For this, some classic authors of each theoretical orientation are chosen according to the influence of their interpretations. While classical liberals praise economic dependence and criticize the political struggle to overcome the colonial and neo-colonial heritage, nationalists and Marxists, in different ways, criticize dependence and propose to overcome it politically. Marxists have never been in power in Brazil, but a pendulum between liberals and nationalists is clear. The relevance of the proposed classification is illustrated by recalling that, today, Brazil is governed by a leader in the Latin American authoritarian neoliberalism tradition inaugurated by Augusto Pinochet in 1973. However, shortly after commemorating 200 years of political independence on September 07th, 2022, the presidential elections in October 2022 may set a new swing in the pendulum toward a nationalist vision of the Brazilian past and future.